Brand Categorization Process for Staple Goods: Comparison between Rural and Urban Customers - Kashyap, Manash Pratim (Information Management and Business Review, 2011)
The main purpose of the paper is to measure and compare the awareness set, consideration set and choice set of rural and urban population. The brand categorization process in an important aspect of consumer behavior and is useful in understanding how a consumer chooses a particular brand. The focus of this work is to compare the brand categorization process of rural and urban consumers. The consumer’s choice process, on some selected staple goods viz. rice, salt, edible oil and tea for rural and urban customers are considered. The study reaches the conclusion that the awareness set size and the consideration set size does not differ significantly for urban and rural consumers but the choice set size differs for rice. For salt and edible oil the rural customers seems to be more aware though there consideration set size and choice set size do not show any significant difference. However, for tea the urban folk have a bigger consideration set and choice set compared to the rural population.